Simultaneous measurement method and error analysis of the six degrees-of-freedom motion errors of a rotary axis - Bao, C.; Feng, Q. (Applied Sciences, 2018)
Error measurement of a rotary axis is the key to error compensation and to improving motion accuracy. However, only a few instruments can measure all the motion errors of a rotary axis. In this paper, a device based on laser collimation and laser interferometry was introduced for simultaneous measurement of all six degrees-of-freedom motion errors of a rotary axis. Synchronous rotation of the target and reference rotary axes was achieved by developing a proportional-integral-derivative algorithm. An error model for the measuring device was established using a homogeneous transformation matrix. The influences of installation errors, manufacturing errors, and error crosstalk were studied in detail, and compensation methods for them were proposed. After compensation, the repeatability of axial and radial motion errors was significantly improved. The repeatability values of angular positioning error and of tilt motion error around the y axis and x axis were 28.0'' 2.8'' and 3.9'' The repeatability values of translational motion errors were less than 2.8 µm. The comparison experiments show that the comparison errors of angular positioning error and tilt motion error around the y axis were 2.3''and 2.9'' respectively. These results demonstrate the effectiveness of our method and the error compensation model.